Resilience Mediates the Relationship Between Social Support and Quality of Life in Patients With Primary Glaucoma - Wang, Yiwen; Zhao, Ying; Xie, Sisi; Wang, Xinru; Chen, Qing; Xia, Xiaobo (Frontiers in Psychiatry, 2019)
Objective: Glaucoma is a serious disease causing blindness, which seriously affects the quality of life of patients. Previous studies have reported that both resilience and social support play important roles in enhancing the quality of life of patients with some diseases. The purpose of this study is to investigate if resilience mediates the relationship between social support and quality of life in patients with primary glaucoma. Methods: We conducted a cross-sectional study with 120 patients with primary glaucoma in China. The Connor-Davidson Resilience Scale was used to measure resilience, and social support was measured by the Perceived Social Support Scale. The Glaucoma Quality of Life-15 questionnaire was used to measure quality of life. Results: There were significant positive correlations between all dimensions and total scores on the resilience, social support, and quality of life scales (p < 0.01). Both resilience and social support could predict these patients’ quality of life. A bootstrap test showed that resilience had a partial mediating effect on the relationship between social support and quality of life (p < 0.05). Conclusion: Resilience mediates the relationship between social support and quality of life in primary glaucoma patients. This finding suggests that increasing resilience and social support can improve the quality of life of primary glaucoma patients in clinical practice.